2021
DOI: 10.1088/1757-899x/1062/1/012025
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of the UTAUT Model to Understand the Technology Adoption of MOOC at Public Universities

Abstract: MOOC is a national agenda in the institutions as it is addressed in the 11th Malaysian Plan, the National Economic Model, Economic Transformation Programme and the Malaysian Education Blueprint. Recently, have witnessed the development of massive open online courses (MOOCs) as a learning trend in the field of open distance education and online learning. As it is considering new technology for us, a research towards its acceptance is essential. This study examines the adoption of MOOC deployment among students … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 6 publications
2
10
1
Order By: Relevance
“…They believe that online learning improves knowledge in a certain course when they are supported with the use of relevant infrastructure and technology, e.g., the internet, Wi-Fi, specific location, and information and communication technology literate. This corresponds with the results of Haron et al (2020) and Nawaz and Mohamed (2020), demonstrating that facilitating conditions significantly influence university students' propensity of adopting mobile learning. Furthermore, an investigation by Toufaily et al (2018) also suggests that to increase the online learning experience, the Internet infrastructure needs to be upgraded to ensure that students can get efficiently connected to their instructors and learning resources via the online learning platform.…”
Section: Facilitating Conditionssupporting
confidence: 88%
See 2 more Smart Citations
“…They believe that online learning improves knowledge in a certain course when they are supported with the use of relevant infrastructure and technology, e.g., the internet, Wi-Fi, specific location, and information and communication technology literate. This corresponds with the results of Haron et al (2020) and Nawaz and Mohamed (2020), demonstrating that facilitating conditions significantly influence university students' propensity of adopting mobile learning. Furthermore, an investigation by Toufaily et al (2018) also suggests that to increase the online learning experience, the Internet infrastructure needs to be upgraded to ensure that students can get efficiently connected to their instructors and learning resources via the online learning platform.…”
Section: Facilitating Conditionssupporting
confidence: 88%
“…Attuquayefio and Addo (2014) investigated students' attitudes toward ICT use and discovered that social influence favourably affected behavioural intentions to use ICT for studying. Haron et al (2020) also found that social influence had a major impact on students' willingness to use MOOC technology, particularly at public universities. Meanwhile, a study by Bharati and Srikanth (2018) discovered that social influence had a negligible consequence on students' intentions of using technology in their learning.…”
Section: Teaching-related Aspectsmentioning
confidence: 89%
See 1 more Smart Citation
“…According to Ajzen [33], BI is also perceived as having a direct influence on adoption. In the MOOCs adoption literature, studies have shown that the BI to use these courses has a strong effect on the actual use of these courses [21,36]. Thus, this study proposes the following hypothesis: Hypothesis 1 (H1).…”
Section: Behavioral Intention and Actual Use Of Moocsmentioning
confidence: 89%
“…The UTAUT [19] is based on eight theories and models: namely, the technology acceptance model (TAM), the theory of reasoned action (TRA), the motivational model (MM), the TPB, the combined TAM TPB model (C-TAM-TPB), the model of PC utilization (MPCU), the innovation diffusion theory (IDT), and the social cognitive theory (SCT). Although UTAUT is not as widely used as TAM, it has garnered academic interest in recent years for its ability to determine user acceptance of MOOCs [21], as demonstrated in Figure 2. According to Venkatesh [19], the eight models explain between 17% and 53% of the variance in users' intentions to use information systems (ISs)/information technology (IT).…”
Section: The Unified Theory Of Acceptance and Use Of Technology (Utaut)mentioning
confidence: 99%